2017
DOI: 10.1177/2047487317744045
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid level predicts adverse outcomes after myocardial revascularization or cardiac valve surgery

Abstract: Background High levels of serum uric acid have been associated with adverse outcomes in cardiovascular diseases such as myocardial infarction and heart failure. The aim of the current study was to evaluate the prognostic role of serum uric acid levels in patients undergoing cardiac rehabilitation after myocardial revascularization and/or cardiac valve surgery. Design We performed an observational prospective cohort study. Methods The study included 1440 patients with available serum uric acid levels, prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
3
21
1
1
Order By: Relevance
“…Clinical studies also indicated the association between UA and several cardiovascular diseases such as hypertension [22], coronary artery disease [23], heart failure [24] and atrial fibrillation [25]. Increased UA level was also found to be risk factor of cardiovascular disease mortality [13], poorer outcome after coronary artery bypass grafting and cardiac valve surgery [14,15].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Clinical studies also indicated the association between UA and several cardiovascular diseases such as hypertension [22], coronary artery disease [23], heart failure [24] and atrial fibrillation [25]. Increased UA level was also found to be risk factor of cardiovascular disease mortality [13], poorer outcome after coronary artery bypass grafting and cardiac valve surgery [14,15].…”
Section: Discussionmentioning
confidence: 96%
“…Several experimental and human studies have shown the association between serum UA level and endothelial dysfunction [10], oxidative stress [11] and systemic inflammation [12]. Epidemiological studies suggested that increased serum UA level was associated with increased cardiovascular disease mortality [13], poorer survival after coronary artery bypass grafting and cardiac valve surgery [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Our model suggests a significant association between hyperuricemia and an adverse outcome of depressive symptoms. It has been shown that elevated serum uric acid levels predict adverse outcomes after myocardial revascularisation or cardiac valve surgery [43]. Some authors maintain that the purinergic system is involved in the regulation of mood [44, 45], but current data regarding the relationship between serum uric acid levels and depression is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…One study shows that during a follow up of 2-3 years, with increase of serum UA level in CHD patients about 60 years old, the risk of all-cause mortality and cardiac death increases significantly [10] . Baseline serum UA level presents favorable values in evaluating and predicting the prognosis of patients with different subtypes of ACS [11][12][13][14] . In fact, hyperuricemia is closely related to DM.…”
Section: Introductionmentioning
confidence: 99%